2013
DOI: 10.1007/s10552-013-0288-8
|View full text |Cite
|
Sign up to set email alerts
|

Eating frequency and risk of colorectal cancer

Abstract: Purpose Eating frequency is a modifiable aspect of dietary behavior that may affect risk of colorectal cancer (CRC). Although most previous case-control studies indicate a positive association, two prospective studies suggest an inverse association between eating frequency and CRC risk, with evidence of effect modification by diet composition. We examined the association between eating frequency and CRC in a large, prospective cohort study, and explored whether this relationship was modified by sex, coffee con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The full list of studies included [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] and their main characteristics are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The full list of studies included [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] and their main characteristics are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence also suggests that dietary behaviours related to lower daily eating frequency (EF) may negatively influence the diet quality (9)(10)(11) and the metabolic health of humans (12) , including the risk of developing cancer (13,14) . Specifically for BC, one single study, to our knowledge, found that a lower number of daily eating episodes in healthy women would be related to the increase in biomarkers linked to systemic inflammation and, consequently, to an increased risk of developing the disease, but the study did not evaluate the impact on diet quality (13) .…”
mentioning
confidence: 99%
“…It has been suggested that eating frequently results in an increased secretion of bile acids into the gut lumen and that dehydroxylation and deconjugation by colonic bacteria induce these bile acids to convert into secondary bile acids, which may have tumourigenic effects (48,49) . However, prospective studies suggest an inverse association between eating frequency and CRC risk, with evidence of effect modification by diet composition (50) . People spend most of their lives in the postprandial state since the true fasting state occurs only in the last 2 h of a regular night sleep (51) ; therefore, quality of food consumed will be key in the effect on health.…”
Section: Discussionmentioning
confidence: 99%